Design, Synthesis, and Antiproliferative Activity of 3,4-Diarylpyrazole-1-carboxamide Derivatives Against Melanoma Cell Line - El-Gamal, Mohammed I.; Choi, Hong Seok; Cho, Hae-Guk; Hong, Jun Hee; Yoo, Kyung Ho; Oh, Chang-Hyun (WILEY-V C H VERLAG GMBH, 2011)
Synthesis of a new series of 3,4-diarylpyrazole-1-carboxamide derivatives is described. Their antiproliferative activity against A375P human melanoma cell line was tested and the effect of substituents on the diarylpyrazole scaffold was investigated. The biological results indicated that five synthesized compounds (Ig, Ii, IIc, IIg, and IIh) exhibited similar activity to Sorafenib. In addition, three compounds (IIa, IIb, and IIi) were more potent than Sorafenib. Among all of these derivatives, compound IIa which has dimethylamino and phenolic moieties showed the most potent antiproliferative activity against A375P human melanoma cell line. Virtual screening was carried out through docking of the most potent compound IIa into the domain of V600E-b-Raf and the binding mode was studied.
Keywords: REFRACTORY SOLID TUMORS; FACTOR RECEPTOR INHIBITOR; RAF KINASE; METASTATIC MELANOMA; PHASE-I; BAY-43-9006; SORAFENIB; THERAPY; PHARMACOKINETICS; INTERLEUKIN-2